درجة ممارسة القيادات النسائية بإدارة تعليم الرياض للتمكين الإداري - عون، وفاء بنت محمد وهبو; اليامي، هادية علي (رابطة التربية الحديثة, 2016)
هدفت هذه الدراسة إلى التعرف علي واقع ممارسة القيادات النسائية في إدارة تعليم مدينة الرياض للتمكين الإداري من وجهة نظر المشرفات التربويات في الإدارات النسائية التابعة لمكتب المساعد للشئون التعليمية في الإدارة العامة للتربية والتعليم بمدينة الرياض. وتسعى الدراسة إلى تحقيق الأهداف التالية: 1. التعرف على درجة ممارسة التمكين الإداري للقيادات الإدارية في إدارة تعليم الرياض من وجهة نظر المشرفات التربويات. 2. تحديد الفروق ذات الدلالة الإحصائية –إن وجدت- في استجابة المشرفات التربويات حول درجة ممارسة التمكين الإداري للقيادات النسائية في إدارة تعليم الرياض تعزي لمتغيرات الدراسة (المؤهل الدراسي، سنوات الخبرة، الإدارة التابعة لها). 3. الكشف عن المعوقات التي تحد من ممارسة التمكين الإداري للقيادات النسائية في إدارة تعليم الرياض من وجهة نظر المشرفات التربويات. ولتحقيق أهداف الدراسة، قامت الباحثة باستخدام المنهج الوصفي المسحي، وجمع البيانات عن طريق الاستبانة التي وجهتها إلى عينة عشوائية نسبية مكونة من (69) مشرفة تربوية من مجتمع الدراسة الأصلي البالغ (346) مشرفة تربوية في الإدارات النسائية التابعة لمكتب المساعد للشئون التعليمية في الإدارة العامة للتربية والتعليم بمدينة الرياض، وقد توصلت الدراسة إلى مجموعة من النتائج من أبرزها ما يلي: 1. أن درجة ممارسة التمكين الإداري من قبل القيادات النسائية بإدارة التربية والتعليم بمنطقة الرياض للتمكين الإداري من وجهة نظر المشرفات التربويات كانت بدرجة مرتفعة، حيث جاء بعد الثقة بالدرجة الأولى يليه بعد التفويض بالمرتبة الثانية وجاء بعد انسياب المعلومات في المرتبة الأخيرة. 2. لا توجد فروق ذات دلالة إحصائية بين درجة ممارسة القيادات النسائية للتمكين النسائي تعزي للمؤهل العلمي وسنوات الخبرة. 3. توجد فروق ذات دلالة إحصائية بين درجة ممارسة القيادات النسائية للتمكين الإداري وبين نوع الإدارة التابعة لها المشرفة. 4. كان هناك موافقة بين أفراد عينة الدراسة حول المعوقات التي تحد من التمكين الإداري وكان أبرز المعوقات ما يلي: المركزية في ممارسة العمل، وعدم وجود توصيف دقيق للمهام، وعدم اختيار القيادات بناء على الكفايات. وقد انتهت الدراسة بعدد من التوصيات والمقترحات.
This study aimed to identify the reality of the level of administrative empowerment of female leaders in education department of Riyadh from the perspective of school inspectors in the women's departments of the Office of the Assistant for Educational Affairs In education department of Riyadh. The objectives of this study summarized as follows: 1. Identify the level of administrative empowerment of female leaders in education department of Riyadh from the perspective of school inspectors. 2. Identify statistical differences, if any, about response of school inspectors toward the level of administrative empowerment of female leaders in education department of Riyadh in accordance with the following variables (years of experience, Degree and Department). 3. Identify the barriers that limit administrative empowerment of female leaders in Education department of Riyadh from the perspective of school inspectors. In order to achieve the objectives of this study, the researcher used a descriptive analytical method. The data collected by a questionnaire sent out to a sample of 69-school inspectors of the original study population of 346-school inspectors in the women's departments of the Office of the Assistant for Educational Affairs In education department of Riyadh. The most significant results of the study are as follows: 1. The female administrative empowerment level rated as high from the perspective of school inspectors in education department of Riyadh. This result came from the dimension of trust as the most important dimension. The dimension of the Authorization came in second place. The dimension of the flow of knowledge and information came at last. 2. Did not observe any statistically significant differences on the level of of the administrative empowerment regard to criterias of (years of experience and Degree). 3. There are statistically significant differences on the level of of the administrative empowerment regard to criterias of (Department of the school inspector). 4. There is a consensus among the members of the study sample about the barriers that limit administrative empowerment of female leaders in Education department of Riyadh. These barriers have been identified as follows: Work centralization, the poor description of the tasks and the selection of leaders not based on efficiency. The study concluded with a number of recommendations and suggestions.
Keywords: القيادات النسائية -- التمكين الإداري -- القيادة الإدارية -- رياض الأطفال